The negotiator - Di Lorenzo, Melinda, 1977- (Harlequin romantic suspense, 2021)
"Norah Loblaw is an expert at negotiating the returns of kidnapped children. But she finds herself in deep when a man claiming to be a cop whisks her off the street. Jacob Pratt needs her to get his nephew back--and despite his unorthodox approach, she's inclined to help. But this is the toughest negotiation Norah's ever faced, and when she finds herself falling for Jacob, the stakes only get higher..."--